Prevalence of non-alcoholic fat disease liver in Russian Federation: meta-analysis - Igor V. Maev; Dmitry N. Andreev; Yury A. Kucheryavyy (ZAO "Consilium Medicum", 2023)
Aim. To systematize data on the prevalence of non-alcoholic fatty liver disease (NAFLD) in the adult population of Russia. Materials and methods. The studies were searched in the MEDLINE/PubMed and RSCI electronic databases from January 2000 to December 2022 (inclusive). The search included relevant publications in peer-reviewed periodicals in English or Russian; publications with data from cross-sectional/epidemiological studies assessing the prevalence of NAFLD in the Russian population; studies on adult patients with NAFLD; publications with detailed descriptive statistics that allow using the data in the meta-analysis. Results. The final analysis included 5 studies involving 96.680 subjects. The overall prevalence of NAFLD in the five adult studies analyzed was 27.562% (95% confidence interval CI 19.05636.979). The analysis used a random effect model, as there was significant heterogeneity between the results in both groups (I2=99.87%; p0.0001). In the studies enrolling patients before 2015, the overall prevalence of NAFLD was 22.409% (95% CI 11.55035.615), whereas, in studies that enrolled patients after 2015, it was 35.874% (95% CI 28.09444.046). When analyzing multicenter studies only, the overall prevalence of NAFLD was 31.975% (95% CI 24.67039.755). Conclusion. This meta-analysis demonstrated that NAFLD is a widespread chronic liver disease in the adult population of Russia, affecting approximately one in four country residents. For a more accurate objectification of the epidemiological structure of NAFLD in Russia, further multicenter studies of unified design are required.